Happiness and mental health of older adults: multiple mediation analysis - Sun, Yujin (Frontiers in Psychology, 2023)
Introduction This study aims to explore the influence mechanism of older adult mental health. As the aging population grows, the mental health of older adults becomes a significant public health and social issue, with happiness serving as a key dimension of mental health. Methods This study utilizes public data from CGSS to investigate the relationship between happiness and mental health, with Process V4.1 used for mediating effects analysis. Results The findings suggest a positive predictive effect of happiness on mental health, with three mediating paths identified: independent mediating effect paths of income satisfaction and health, as well as a multiple mediating effects path through income satisfaction and health. Discussion The study suggests that improving the multi-subject mental health support service system for older adults and creating public values for mental health risk coping mechanisms. This helps to understand the complex relationship between aging on individual and social levels. These results provide empirical support for healthy aging among older adults and future policymaking.